2021
DOI: 10.15366/rimcafd2021.82.008
|View full text |Cite
|
Sign up to set email alerts
|

Motivación, Autoconfianza Y Ansiedad en Judo: Sexo Y Nivel Competitivo

Abstract: El objetivo del estudio fue identificar las posibles diferencias a nivel de motivación, autoconfianza y ansiedad que puedan existir en función del sexo y el nivel competitivo de dos grupos de judokas (Grupo de alto rendimiento y Grupo de especialización). Se llevó a cabo un estudio descriptivo de corte transversal. Se administraron el Competitive State Anxiety Inventory (CSAI-2R) y el Behavioral Regulation in Sport Questionnaire (BRSQ) 10 minutos antes de entrar los judocas al tatami, el día de la competición.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Regarding gender differences in profiles, in the present study there were no significant differences. Likewise, Pulido et al 33 , did not find differences in the variables motivation and self-confidence according to sex, nor in the variables motivation and anxiety in the comparison between both groups. In contrast, Pulido et al 33 found significant differences in the comparison between men and women in anxiety, resulting in higher somatic anxiety in women than in men, perceiving the symptoms that cause their physical state, heart rate, sweating, or activation of the nervous system in a more pronounced way.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regarding gender differences in profiles, in the present study there were no significant differences. Likewise, Pulido et al 33 , did not find differences in the variables motivation and self-confidence according to sex, nor in the variables motivation and anxiety in the comparison between both groups. In contrast, Pulido et al 33 found significant differences in the comparison between men and women in anxiety, resulting in higher somatic anxiety in women than in men, perceiving the symptoms that cause their physical state, heart rate, sweating, or activation of the nervous system in a more pronounced way.…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, Pulido et al 33 , did not find differences in the variables motivation and self-confidence according to sex, nor in the variables motivation and anxiety in the comparison between both groups. In contrast, Pulido et al 33 found significant differences in the comparison between men and women in anxiety, resulting in higher somatic anxiety in women than in men, perceiving the symptoms that cause their physical state, heart rate, sweating, or activation of the nervous system in a more pronounced way. The authors indicate that these results could condition judokas in their training, preparation and competition, so it would be advisable to control the somatic anxiety variable in athletes.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, anxiety is a variety of stress answers to a situation perceived as aversive that activates avoidance mechanisms and is characterized by concern and fear about the possibility of harm, whether physical or psychological, which is accompanied by an increase in physiological activation because of the threat assessment (Pineda-Espejel et al, 2019). This construct is understood as an emotion that appears in response to the way competition is interpreted and evaluated (Weinberg and Gould, 2010) and causes negative reactions, worry, and thoughts that can alter attentional processes and other cognitive functions (Silva et al, 2015;Pulido et al, 2021). This is one of the psychological variables that we are going to study, and for this reason, it is necessary to explain and describe its role in the sporting environment.…”
Section: Introductionmentioning
confidence: 99%
“…12 Due to its relationship with sport performance, cognitive anxiety and self-confidence have attracted the attention of both researchers and practitioners. [13][14][15][16][17][18][19][20] Thus, previous studies have investigated the pre-and post-competitive anxiety in athletes. Winner young male soccer players were found to exhibit significantly lower cognitive anxiety and cortisol (a hormone that is released in response to stress or fear by the adrenal glands) as well as higher self-confidence and oxytocin level values than losers.…”
Section: Introductionmentioning
confidence: 99%